2017
DOI: 10.1017/s1468109916000323
|View full text |Cite
|
Sign up to set email alerts
|

China's Assertive Posture in Reinforcing its Territorial and Sovereignty Claims in the South China Sea: An Insight into Malaysia's Stance

Abstract: China's growing assertiveness in strengthening its territorial and sovereignty claims in the South China Sea has arguably intensified friction and deepened tension between the rival claimant States. In sharp contrast to the strong reactions of its fellow ASEAN claimants, such as Vietnam and the Philippines, Malaysia traditionally has been less critical and more inclined to downplay China's perceived emotive actions. This subtle foreign policy orientation is likely to remain unchanged in the immediate future. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
0
4
0
1
Order By: Relevance
“…However, in more recent developments, China faces a difficult mission to gain trust predominantly from Malaysia for reasons specifically related to the changing political landscape, scandals like 1Malaysia Development Berhad (1MDB), disproportionate geopolitical and regional developments in territorial waters and China's stance on humanitarian and health issues. Moreover, it is observed that Xi Jinping has not indicated any change of policy position on the disputes in the South China Sea (Ahmad & Mohd Sani, 2017;.…”
Section: Bri Projects and Developmental Perception In Malaysiamentioning
confidence: 97%
See 1 more Smart Citation
“…However, in more recent developments, China faces a difficult mission to gain trust predominantly from Malaysia for reasons specifically related to the changing political landscape, scandals like 1Malaysia Development Berhad (1MDB), disproportionate geopolitical and regional developments in territorial waters and China's stance on humanitarian and health issues. Moreover, it is observed that Xi Jinping has not indicated any change of policy position on the disputes in the South China Sea (Ahmad & Mohd Sani, 2017;.…”
Section: Bri Projects and Developmental Perception In Malaysiamentioning
confidence: 97%
“…Bentley (2015) also outlined measures that Malaysia should declare publicly to defend its international law. According to Ahmad and Mohd Sani (2017) (Ahmad & Mohd Sani, 2017). Alatas (2021) reiterated that Malaysia is cautious of China but does not consider her an immediate security threat.…”
Section: Bumpy On Land Standoff At Seamentioning
confidence: 99%
“…As mentioned earlier, whether Malaysia is adopting a decisive, strict, or accommodative stance vis-à-vis China in the South China Sea is still unclear. Several of the literature has also shown that Malaysia is currently taking an assertive turn to respond to China's aggressive maneuvers at sea due to the dominant deployment of navies to respond to crises (Noor, 2016;Ahmad and Sani, 2017;Wey, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although Taiwan is still considered an integral part of China, Taiwan also claims ownership of territory in the South China Sea (Ferhat, 2006) (Ahmad & Mohd Sani, 2017). In 1984,…”
Section: Introductionmentioning
confidence: 99%